What explains landscape patterns of tree mortality caused by bark beetle outbreaks in Greater Yellowstone? - Martin Simard; Erinn N. Powell; Kenneth F. Raffa; Monica G. Turner (Global Ecology and Biogeography, 2012)
Aim Bark beetle outbreaks have recently affected extensive areas of western North American forests, and factors explaining landscape patterns of tree mortality are poorly understood. The objective of this study was to determine the relative importance of stand structure, topography, soil characteristics, landscape context (the characteristics of the landscape surrounding the focal stand) and beetle pressure (the abundance of local beetle population eruptions around the focal stand a few years before the outbreak) to explain landscape patterns of tree mortality during outbreaks of three species: the mountain pine beetle, which attacks lodgepole pine and whitebark pine; the spruce beetle, which feeds on Engelmann spruce; and the Douglas‐fir beetle, which attacks Douglas‐fir. A second objective was to identify common variables that explain tree mortality among beetle–tree host pairings during outbreaks. Location Greater Yellowstone ecosystem, Wyoming, USA. Methods We used field surveys to quantify stand structure, soil characteristics and topography at the plot level in susceptible stands of each forest type showing different severities of infestation (0–98% mortality; n = 129 plots). We then used forest cover and beetle infestation maps derived from remote sensing to develop landscape context and beetle pressure metrics at different spatial scales. Plot‐level and landscape‐level variables were used to explain outbreak severity. Results Engelmann spruce and Douglas‐fir mortality were best predicted using landscape‐level variables alone. Lodgepole pine mortality was best predicted by both landscape‐level and plot‐level variables. Whitebark pine mortality was best – although poorly – predicted by plot‐level variables. Models including landscape context and beetle pressure were much better at predicting outbreak severity than models that only included plot‐level measures, except for whitebark pine. Main conclusions Landscape‐level variables, particularly beetle pressure, were the most consistent predictors of subsequent outbreak severity within susceptible stands of all four host species. These results may help forest managers identify vulnerable locations during ongoing outbreaks.